Analisis Hukum Masa Tunggu bagi Perempuan Pasca Pembubaran Perkawinan dalam KUHPerdata: Penelitian - Rika Aryati; Siska Ayu Ningsih (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This research aims to analyze the waiting period for women after the dissolution of marriage in the Civil Code, its development and position. Using normative legal research with a statute approach, conceptual approach, historical approach and analytical approach. The results show that the position of the waiting period in article 34 of the Civil Code is not regulated further, but the Law on Marriage and its Implementing Regulations regulate more specifically the provisions of the waiting period for women who have broken up their marriage. However, the regulation refers to Islamic law, meaning that it cannot be applied equally to other than Muslims, especially after being regulated more explicitly in the Compilation of Islamic Law. In conclusion, the provisions in the Civil Code regarding the waiting period still need to be updated for the sake of legal certainty for non-Muslim women, whether it is abolished or determined otherwise.